The methamphetamine industry in America: transnational cartels and local entrepreneurs - Brownstein, Henry H. (Critical issues in crime and society, 2014)
Preface -- Acknowledgments -- Understanding methamphetamine markets as an industry -- Methamphetamine in America -- Social activity in the methamphetamine industry -- Social relationships in the methamphetamine industry -- Culture and the methamphetamine industry -- Meth markets and the methamphetamine industry in the United States -- Appendix A: study of the dynamics of methamphetamine markets -- References -- Index